INNOVATION MALANG BLACK APPLE - Morell, Gerry; Tanius, Billy; Surjawan, Iwan; Ni Ketut Veri Kusumaningrum (Politeknik Internasional Bali, 2024)
The study focuses on developing innovation in processing Malang Apples through advanced fermentation techniques to create